2014
DOI: 10.1002/pola.27299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, self-assembly, and thermosensitivity of amphiphilic POEGMA-PDMS-POEGMA triblock copolymers

Abstract: In this article, the synthesis and self‐assembly of a novel well‐defined biocompatible amphiphilic POEGMA‐PDMS‐POEGMA triblock copolymer were studied. The copolymer was synthesized by atom transfer radical polymerization of oligo(ethylene glycol) methyl ether methacrylate (OEGMA) using α,ω‐dibromo polydimethylsiloxane macroinitiator (Br‐PDMS‐Br). Br‐PDMS‐Br was synthesized through the esterification of α,ω‐hydroxypropyl polydimethylsiloxane and 2‐bromoisobutyryl bromide. The structures of the copolymers were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…The shape and size of PDMS-g-POEM comb copolymer with a molecular weight of 14,000 gmol -1 in ethanol (1 wt%) are comparable to those reported by Wang et al 29 ; these authors reported that a POEGMA 11.6 -PDMS 11 - 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 POEGMA 11.6 triblock copolymer with a molecular weight of 9400 gmol -1 could self-assemble into spherical single micelles with a diameter of approximately 100 nm in aqueous solution (0.5 mg mL -1 ).…”
Section: Characterization Of Pdms-g-poem Comb Copolymersupporting
confidence: 87%
See 1 more Smart Citation
“…The shape and size of PDMS-g-POEM comb copolymer with a molecular weight of 14,000 gmol -1 in ethanol (1 wt%) are comparable to those reported by Wang et al 29 ; these authors reported that a POEGMA 11.6 -PDMS 11 - 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 POEGMA 11.6 triblock copolymer with a molecular weight of 9400 gmol -1 could self-assemble into spherical single micelles with a diameter of approximately 100 nm in aqueous solution (0.5 mg mL -1 ).…”
Section: Characterization Of Pdms-g-poem Comb Copolymersupporting
confidence: 87%
“…The self-arrangement of PDMS-g-POEM comb copolymer into uniform spherical micelles in a polar solvent such as ethanol was proved by the EF-TEM image shown in [26][27][28][29] Micelle morphology is largely dependent on experimental parameters such as the molecular weight of the polymers, relative chain length ratio of each block, type of medium, and concentration. The shape and size of PDMS-g-POEM comb copolymer with a molecular weight of 14,000 gmol -1 in ethanol (1 wt%) are comparable to those reported by Wang et al 29 ; these authors reported that a POEGMA 11.6 -PDMS 11 - 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 POEGMA 11.6 triblock copolymer with a molecular weight of 9400 gmol -1 could self-assemble into spherical single micelles with a diameter of approximately 100 nm in aqueous solution (0.5 mg mL -1 ).…”
Section: Characterization Of Pdms-g-poem Comb Copolymermentioning
confidence: 99%
“…100% renewably sourced PO3G is a novel bio‐based polyether glycol, and this kind of renewable polyol with low glass transition temperature ( T g ) and thermal stability was allowed to react with 2‐bromoisobutyryl bromide to yield Br‐PO3G‐Br macroinitiator by esterification following literature procedures . The chemical structure of the resulting Br‐PO3G‐Br was characterized by 1 H NMR, GPC, and FTIR measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The CMC of triblock copolymer samples was determined by the fluorescence probe technique using pyrene as a fluorescence probe according to our previous works …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation